Baseline Sensitivity of Echinochloa crus-gall and E. oryzicola to Florpyrauxifen-Benzyl, a New Synthetic Auxin Herbicide, in Korea - Lim, Soo-Hyun; Kim, Harim; Noh, Tae-Kyeong; Lim, Ji-Soo; Yook, Min-Jung; Kim, Jin-Won; Yi, Jee-Hwan; Kim, Do-Soon (Frontiers in Plant Science, 2021)
Echinochloa species is one of the most problematic weed species due to its high competitiveness and increasing herbicide resistance. Florpyrauxifen-benzyl, a new auxin herbicide, was recently introduced for Echinochloa management; however, the potential risk for the development of herbicide resistance in Echinochloa species has not been well investigated. Thus, this study was conducted to evaluate the baseline sensitivity of Echinochloa species to florpyrauxifen-benzyl to estimate the risk of future resistance development. A total of 70 and 71 accessions of Echinochloa crus-galli and Echinochloa oryzicola were collected from paddy fields in Korea, respectively. These two Echinochloa species were grown in plastic pots up to the 5-leaf stage, and treated with florpyrauxifen-benzyl at a range of doses from 2.2 to 70.0 g a.i. ha-1. Nonlinear regression analyses revealed that GR50 values for E. oryzicola ranged from 4.54 g to 29.66 g a.i. ha-1, giving a baseline sensitivity index (BSI) of 6.53, while those for E. crus-galli ranged from 6.15 g 1 to 16.06 g a.i. ha-1, giving a BSI of 2.61. Our findings suggest that E. oryzicola has a greater potential risk than E. crus-galli for the development of metabolism-based resistance to florpyrauxifen-benzyl.